Comparative Analysis of The Percentage of Poor People in Indonesia Between Urban and Rural Areas in 2023 - Aulia, Rima; Salamah, Naila Putri; Batlayangin, Marciana Siendy; Hajar, Siti (Jurnal Multidisiplin West Science, 2024)
This study aims to compare the poverty rates of rural and urban residents in Indonesia in 2023. Quantitative data comes from the Central Statistics Agency (BPS) in 2023. The analysis methods used include descriptive analysis, normality test, homogeneity test, and Mann-Whitney test. The normality test is conducted to ensure that the distribution of poverty data follows a normal distribution. The homogeneity test tests whether the variance of poverty data in rural and urban areas is the same. The Mann-Whitney test, which is an alternative nonparametric T-test, was used to determine whether there is a significant difference between rural and urban poverty rates, assuming the data is normally distributed or homoskedastic. The results show that there is a large difference in poverty rates between rural and urban areas, where poverty rates in rural areas are higher than in urban areas. These results suggest that more targeted and strategic policy interventions are needed to reduce rural poverty.